Case report: A rare case of oral sebaceous carcinoma in the upper lip - Yousef Katib; Yousef Katib; Murad Essatari (Frontiers Media S.A., 2024)
Sebaceous carcinoma (SC) is a rare aggressive malignant tumor that originates in the adnexal epithelium of the sebaceous gland. While occurrences on the lips are extremely uncommon, there have been a few reported cases in the literature. Our case involves a 47-year-old smoker male who presented with a painless, non-mobile lesion on his upper lip that had been present for 12 months. Upon clinical examination, an ulcerated, exophytic, and irregularly shaped mass was observed on the upper lip. No other intraoral lesions were found. An incisional biopsy was performed, revealing a malignant tumor with a nodular pattern consisting of basaloid cells with obvious sebaceous differentiations and frequent mitoses. The neoplastic cells tested positive for broad-spectrum cytokeratin (AE1-AE3), epithelial membrane antigen (EMA), and P53, while testing negative for S-100 and carcinoembryonic antigen (CEA). Based on these results, a diagnosis of SC of the upper lip was made. This case report and review aimed to describe the histogenesis, unique clinicopathological features, and current treatment options for SC.